THE INFLUENCE OF THE PRESENCE OF FOREIGN ENTREPRENEURS ON THE DEVELOPMENT OF COMMUNITY TOURISM BUSINESS IN KERENG BANGKIRAI - Anggini, Pira; Octavianus, Junnior; Pramana, Dea Fiona; Effrata, Effrata; Marissa, Novaria; Syarif, Akhmad (FISIPOL Universitas PGRI Palangka Raya, 2025)
Kereng Bangkirai, an area located in Central Kalimantan, has become a tourism destination that attracts both local and international attention. The presence of foreign entrepreneurs in this region has a significant impact on the development of the local community's tourism business. This research aims to analyze the influence of foreign entrepreneurs on the growth and development of the tourism sector in Kereng Bangkirai. Using qualitative and quantitative approaches, data was collected through surveys, interviews and literature studies. The research results show that the presence of foreign entrepreneurs not only increases the number of tourist visits, but also contributes to increasing local community income and developing better infrastructure. However, there are also challenges to be faced, including potential negative impacts on local culture and unhealthy competition.